I need help with this inverse problem...Im no good in math. f(x)=(x+2)^3-4
Follow Math Help Forum on Facebook and Google+
Originally Posted by bastropgarl I need help with this inverse problem...Im no good in math. f(x)=(x+2)^3-4 $\displaystyle y = (x+2)^3 - 4$ The key is to isolate x in terms of y. $\displaystyle x = \sqrt[3]{y+4} - 2$ Then replace $\displaystyle x$ with $\displaystyle f^{-1}(x)$ and $\displaystyle y$ with $\displaystyle x$ $\displaystyle f^{-1}(x) = \sqrt[3]{x+4} - 2$
View Tag Cloud